Estimation of some Elements and Acids for the Different Grape Juice - Jamil, Dalia M (Al-Nahrain Journal of Science, 2018)
This study included estimating the heavy elements of some types of grape juice of different origin and determining their proportions in juices and comparing them with the quality control of Iraq and observing whether it is suitable for human use or not. Calcium salts are observed as 137 ppm in C juice and 9.5 ppm of magnesium in juice B, for heavy metals the highest percentage of lead 0.19ppm recorded in juice A, 1.7 ppm of copper in B juice 3.5 ppm Iron in juice A, 0.8 ppm of zinc in B juice and A, 0.06 ppm of aluminum in B, 0.015 ppm of cobalt in juice A and B, 0.06 ppm of nickel in B juice, Sodium was 168.1 ppm in C juice, but the acids were found to have the highest rates were 3.1 ppm of malic acid in B, 156.7 ppm of acid in Juice of ascorbic B, 238.5 ppm of acid found in lemon juice 130ppm in juice B.